Epidemiology of Burn Deaths in Aurangabad Region, India - Tasgaonkar, G V; Meshram, V P; Khartade, H K; Zine, K U; Kamble, R M; Hosmani, A H (International Journal of Medical Toxicology and Forensic Medicine, 2016)
Background: Amongst all discoveries by men, barely few like cultivation of soil, speech and writing, have borne such significant developments as has finding out how to make fire. From the discovery of fire and its tremendous force, manufacturing, transportation and practically all phases of modern industrial life emerged out. Burns are injuries often produced by contact with dry heat, such as flame, radiation, or some solid heated material like metal or glass to the body. Methods: This study was conducted prospectively on 325 cases of death due to burns in the period from January 2010 to December 2010. Results: Hindu married females belonging to rural background were most common victims of burns. Maximum cases were observed in the evening with involvement of cooking apparatus most of the time. Conclusion: The present study has findings more or less consistent with the findings of the other Indian studies. Rising incidences of burns can be prevented by awareness and education about the hazards of fire and safety measures also upgrade of social and educational standards of population.